- 重要公式
▽ ⋅ ( A ⃗ × B ⃗ ) = B ⃗ ⋅ ▽ × A ⃗ − A ⃗ ⋅ ▽ × B ⃗ \triangledown \cdot(\vec A \times \vec B)= \vec B \cdot \triangledown \times\vec A-\vec A\cdot\triangledown\times\vec B ▽⋅(A×B)=B⋅▽×A−A⋅▽×B - 证明
▽ = ∂ ∂ x e ⃗ x + ∂ ∂ y e ⃗ y + ∂ ∂ z e ⃗ z \triangledown=\frac{\partial}{\partial x}\vec e_x+\frac{\partial }{\partial y}\vec e_y+\frac{\partial }{\partial z}\vec e_z ▽=∂x∂ex+∂y∂ey+∂z∂ez
A ⃗ × B ⃗ = ∣ e ⃗ x e ⃗ y e ⃗ z A x A y A z B x B y B z ∣ = ( A y B z − A z B y ) e ⃗ x + ( A z B x − A x B z ) e ⃗ y + ( A x B y − A y B x ) e ⃗ z \vec A \times \vec B=\left | \begin{matrix} \vec e_x &\vec e_y &\vec e_z\\ A_x & A_y & A_z\\ B_x & B_y & B_z \end{matrix} \right |\\ =(A_yB_z-A_zB_y)\vec e_x+(A_zB_x-A_xB_z)\vec e_y+(A_xB_y-A_yB_x)\vec e_z A×B=∣∣∣∣∣∣exAxBxeyAyByezAzBz∣∣∣∣∣∣=(AyBz−AzBy)ex+(AzBx−AxBz)ey+(AxBy−AyBx)ez
▽ ⋅ ( A ⃗ × B ⃗ ) = ( ∂ ∂ x e ⃗ x + ∂ ∂ y e ⃗ y + ∂ ∂ z e ⃗ z ) ⋅ ( ( A y B z − A z B y ) e ⃗ x + ( A z B x − A x B z ) e ⃗ y + ( A x B y − A y B x ) e ⃗ z ) = ∂ ( A y B z − A z B y ) ∂ x + ∂ ( A z B x − A x B z ) ∂ y + ∂ ( A x B y − A y B x ) ∂ z = ∣ ∂ ∂ x ∂ ∂ y ∂ ∂ z A x A y A z B x B y B z ∣ \triangledown \cdot(\vec A \times \vec B)=(\frac{\partial}{\partial x}\vec e_x+\frac{\partial }{\partial y}\vec e_y+\frac{\partial }{\partial z}\vec e_z) \cdot\bigg((A_yB_z-A_zB_y)\vec e_x+(A_zB_x-A_xB_z)\vec e_y+(A_xB_y-A_yB_x)\vec e_z\bigg)\\ =\frac{\partial{(A_yB_z-A_zB_y)}}{\partial x}+\frac{\partial{(A_zB_x-A_xB_z)}}{\partial y}+\frac{\partial{(A_xB_y-A_yB_x)}}{\partial z}\\ =\left | \begin{matrix} \frac{\partial}{\partial x}&\frac{\partial }{\partial y}&\frac{\partial }{\partial z}\\ A_x & A_y & A_z\\ B_x & B_y & B_z \end{matrix} \right |\\ ▽⋅(A×B)=(∂x∂ex+∂y∂ey+∂z∂ez)⋅((AyBz−AzBy)ex+(AzBx−AxBz)ey+(AxBy−AyBx)ez)=∂x∂(AyBz−AzBy)+∂y∂(AzBx−AxBz)+∂z∂(AxBy−AyBx)=∣∣∣∣∣∣∂x∂AxBx∂y∂AyBy∂z∂AzBz∣∣∣∣∣∣
B ⃗ ⋅ ▽ × A ⃗ − A ⃗ ⋅ ▽ × B ⃗ = B ⃗ ⋅ ∣ e ⃗ x e ⃗ y e ⃗ z ∂ ∂ x ∂ ∂ y ∂ ∂ z A x A y A z ∣ − A ⃗ ⋅ ∣ e ⃗ x e ⃗ y e ⃗ z ∂ ∂ x ∂ ∂ y ∂ ∂ z B x B y B z ∣ = ( B x e ⃗ x + B y e ⃗ y + B z e ⃗ z ) ⋅ ( ( ∂ A z ∂ y − ∂ A y ∂ z ) e ⃗ x + ( ∂ A x ∂ z − ∂ A z ∂ x ) e ⃗ y + ( ∂ A y ∂ x − ∂ A x ∂ y ) e ⃗ z ) − ( A x e ⃗ x + A y e ⃗ y + A z e ⃗ z ) ⋅ ( ( ∂ B z ∂ y − ∂ B y ∂ z ) e ⃗ x + ( ∂ B x ∂ z − ∂ B z ∂ x ) e ⃗ y + ( ∂ B y ∂ x − ∂ B x ∂ y ) e ⃗ z ) = B x ( ∂ A z ∂ y − ∂ A y ∂ z ) + B y ( ∂ A x ∂ z − ∂ A z ∂ x ) + B z ( ∂ A y ∂ x − ∂ A x ∂ y ) − ( A x ( ∂ B z ∂ y − ∂ B y ∂ z ) + A y ( ∂ B x ∂ z − ∂ B z ∂ x ) + A z ( ∂ B y ∂ x − ∂ B x ∂ y ) ) ∵ B z ∂ A y ∂ x − B y ∂ A z ∂ x + A y ∂ B z ∂ x − A z ∂ B y ∂ x = ( B z ∂ A y ∂ x + A y ∂ B z ∂ x ) − ( B y ∂ A z ∂ x + A z ∂ B y ∂ x ) = ∂ ( A y B z ) ∂ x − ∂ ( A z B y ) ∂ x = ∂ ( A y B z − A z B y ) ∂ x \vec B \cdot \triangledown \times\vec A-\vec A\cdot\triangledown\times\vec B=\vec B \cdot \left | \begin{matrix} \vec e_x &\vec e_y &\vec e_z\\ \frac{\partial}{\partial x}&\frac{\partial }{\partial y}&\frac{\partial }{\partial z}\\ A_x & A_y & A_z \end{matrix} \right | - \vec A \cdot \left | \begin{matrix} \vec e_x &\vec e_y &\vec e_z\\ \frac{\partial}{\partial x}&\frac{\partial }{\partial y}&\frac{\partial }{\partial z}\\ B_x & B_y & B_z \end{matrix}\right | \\ = (B_x\vec e_x+B_y\vec e_y+B_z\vec e_z)\cdot\bigg( (\frac{\partial A_z}{\partial y}-\frac{\partial A_y}{\partial z})\vec e_x+(\frac{\partial A_x}{\partial z}-\frac{\partial A_z}{\partial x})\vec e_y+(\frac{\partial A_y}{\partial x}-\frac{\partial A_x}{\partial y})\vec e_z \bigg)\\ -(A_x\vec e_x+A_y\vec e_y+A_z\vec e_z)\cdot\bigg( (\frac{\partial B_z}{\partial y}-\frac{\partial B_y}{\partial z})\vec e_x+(\frac{\partial B_x}{\partial z}-\frac{\partial B_z}{\partial x})\vec e_y+(\frac{\partial B_y}{\partial x}-\frac{\partial B_x}{\partial y})\vec e_z \bigg)\\ =B_x( \frac{\partial A_z}{\partial y}-\frac{\partial A_y}{\partial z})+ B_y(\frac{\partial A_x}{\partial z}-\frac{\partial A_z}{\partial x})+ B_z(\frac{\partial A_y}{\partial x}-\frac{\partial A_x}{\partial y})\\ -\bigg(A_x( \frac{\partial B_z}{\partial y}-\frac{\partial B_y}{\partial z})+ A_y(\frac{\partial B_x}{\partial z}-\frac{\partial B_z}{\partial x})+ A_z(\frac{\partial B_y}{\partial x}-\frac{\partial B_x}{\partial y})\bigg)\\ \because B_z\frac{\partial A_y}{\partial x}-B_y\frac{\partial A_z}{\partial x}+ A_y\frac{\partial B_z}{\partial x}- A_z\frac{\partial B_y}{\partial x}= \bigg(B_z\frac{\partial A_y}{\partial x}+ A_y\frac{\partial B_z}{\partial x}\bigg)-\bigg(B_y\frac{\partial A_z}{\partial x}+A_z\frac{\partial B_y}{\partial x} \bigg)\\ =\frac{\partial( A_yB_z)}{\partial x}-\frac{\partial( A_zB_y)}{\partial x}=\frac{\partial( A_yB_z-A_zB_y)}{\partial x} B⋅▽×A−A⋅▽×B=B⋅∣∣∣∣∣∣ex∂x∂Axey∂y∂Ayez∂z∂Az∣∣∣∣∣∣−A⋅∣∣∣∣∣∣ex∂x∂Bxey∂y∂Byez∂z∂Bz∣∣∣∣∣∣=(Bxex+Byey+Bzez)⋅((∂y∂Az−∂z∂Ay)ex+(∂z∂Ax−∂x∂Az)ey+(∂x∂Ay−∂y∂Ax)ez)−(Axex+Ayey+Azez)⋅((∂y∂Bz−∂z∂By)ex+(∂z∂Bx−∂x∂Bz)ey+(∂x∂By−∂y∂Bx)ez)=Bx(∂y∂Az−∂z∂Ay)+By(∂z∂Ax−∂x∂Az)+Bz(∂x∂Ay−∂y∂Ax)−(Ax(∂y∂Bz−∂z∂By)+Ay(∂z∂Bx−∂x∂Bz)+Az(∂x∂By−∂y∂Bx))∵Bz∂x∂Ay−By∂x∂Az+Ay∂x∂Bz−Az∂x∂By=(Bz∂x∂Ay+Ay∂x∂Bz)−(By∂x∂Az+Az∂x∂By)=∂x∂(AyBz)−∂x∂(AzBy)=∂x∂(AyBz−AzBy)
- 同理其他三项可得,证毕